Study on ultraviolet absorption characteristics of SF6 decomposition components. Issue 1 (October 2020) - Shiling, Zhang; Qiang, Yao
Abstract: Establish the UV spectrum database of the SF6 characteristic decomposition components: Based on the previous research and simulation analysis, obtain the UV spectrum of the SF6 characteristic decomposition components, and establish the corresponding database. Through the analysis of a large number of actual test data, the ultraviolet spectrum database of SO2, CS2 and H2S is obtained and established to realize the quantitative analysis of SO2, CS2 and H2S. The detection accuracy of H2S and the SO2 reaches 10 −6 level, and that of the CS2 reaches 10 −9 level, realizing the low concentration quantitative detection of SF6 characteristic components. The detection of SO2, CS2 and H2S in gas insulated equipment can effectively predict and diagnose the occurrence of partial discharge fault, partial overheating fault and solid insulation fault in gas insulated equipment. As the symbol gas, the generation of H2S directly indicates the occurrence of more serious partial overheating or partial discharge fault, while SO2 is the characteristic component gas. The occurrence of CS2 indicates that there may be a local fault involving solid insulating medium in the equipment. The detection of three gases can provide important conditions for on-line monitoring of gas insulated equipment.